Scientific Literacy Assistance for Children in Lombu Village, Southwest Sumba Regency - Yohanis U. Kaleka; Yohanes Engge; Yulita Adelfin Lede (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Science literacy is included in one of the science skills that children should possess and is part of the national literacy movement to increase low literacy among children. Especially on the island of Sumba, it is known that the scientific literacy of children has not increased significantly. Scientific literacy assistance activities have been carried out in Lombu Village, Wewewa Tengah District, Southwest Sumba Regency. The participants of the activity were the children of the Lombu Village, totaling 44 people. The purpose of this assistance is to increase children's understanding of literacy in the Lombu village. The implementation method of this activity consists of several stages including: (1) analysis of needs and potential in the village, (2) interviews with village officials, (3) mapping of literacy program activities , (4) implementation of scientific literacy activities, (5) evaluation of the program and follow-up plan in the Lombu village. The results of the study of this activity show that there is a greater understanding of science through practice with children in Lombu village, especially capillarity science, floating eggs and magic powder.